Diversity And Functional Composition of Ground Dwelling Arthropods in Vegetable Fields of Modoinding District. - Turang, Deflly A. S.; Tairas, Robert William; Paruntu, Meisye H. B.; Kairupan, Grace Amanda (Sam Ratulangi University, 2026)
Ground dwelling arthropods contribute to decomposition, nutrient cycling, and biological control, and their community structure can reflect management intensity in agroecosystems. Intensive vegetable cultivation in Modoinding District, South Minahasa Regency, North Sulawesi, commonly involves routine fertilizer and pesticide use, yet baseline information on soil associated arthropod diversity across major crops remains limited. This study assessed the diversity, functional roles, and population levels of ground dwelling arthropods in vegetable fields using pitfall trapping. Sampling was conducted at ten georeferenced points distributed across key vegetable producing villages, with traps operated for two days and repeated three times. Arthropods were sorted through macroscopic observation and identified using microscopic examination, primarily to order and family levels. Community diversity was quantified using the Shannon Wiener index. Overall, eight orders and seventeen families were recorded, representing decomposers, predators, herbivores, vectors, parasitoids, and omnivores. Decomposer groups, particularly Collembola, were generally dominant in several crop fields, while predator groups such as ants and spiders were also consistently present. Shannon diversity values across host crops ranged from 0.255 to 1.333, indicating low to moderate diversity and suggesting that some fields were characterized by strong dominance of a limited number of taxa. These findings provide baseline data for biomonitoring programs in Modoinding and support the use of ground dwelling arthropod communities as practical indicators to evaluate ecological responses to vegetable production management. Keywords: Collembola, Modoinding, Pitfall trap, Shannon Wiener index, Vegetable fields